A TGAS/Gaia DR1 parallactic distance to the [sigma] Orionis cluster - Caballero, José A. (Astronomische Nachrichten, 2017)
With the new Tycho?Gaia Astrometric Solution (TGAS), I derive a new parallactic distance to the young σ Orionis open cluster, which is a cornerstone region for studying the formation and evolution of stars and substellar objects from tens of solar masses to a few Jupiter masses. I started with the list of the 46 brightest cluster stars of Caballero (2007). After identifying the 24 TGAS stars in the 30?arcmin?radius survey area and accounting for 11 FGKM?type dwarfs and giants in the foreground and background, I got a list of 13 cluster members and candidates with new parallaxes. Of them, I discarded five cluster member candidates with questionable features of youth and/or discordant parallaxes and proper motions, including a distant Herbig Ae/Be star, and proceeded with the remaining eight stars. The σ Orionis mean heliocentric distance is , which is consistent with a contemporaneous interferometric determination that concludes a two?decade dispute on the cluster distance. As a by?product, the reclassification of those five cluster member candidates, now interlopers, shows a manifest deficit of cluster stars between 1.2 and 2.1?M?, which leaves the door open to new astrometric membership analyses with the next Gaia data releases.